Implementation of the Cooperative Learning Model to Develop Soft Skill Aspects in Elementary School Students - Zahra, Zhaffa Ramadhani; Hendracipta, Nana; Pribadi, Reksa Adya; Hakim, Zerri Rahman (EduBasic Journal: Jurnal Pendidikan Dasar, 2024)
The current shift in the educational paradigm can be observed in Indonesia's emphasis on developing 21st-century skills. Soft skills are now a criterion for the quality of human resources, and their acquisition must be habitual. This can begin with classroom learning activities as well as supporting activities outside of the classroom. The purposes of this research were, therefore, to 1) analyze the learning process using the cooperative learning model, 2) apply the cooperative learning model to analyze supporting and inhibiting factors for learning activities, and 3) describe the impact of using the cooperative learning model on developing soft skills in class V students at the Islamic Integrated Elementary School of Irsyadul Ibad, particularly in the class of Hanzalah. In this study, descriptive methods were combined with a qualitative approach, and the data were gathered as a set of words and images. The data from observation, documentation, and interview sources were thus analyzed by the researchers in this study. The study's findings demonstrated that: 1) Students' soft skills can be developed in the classroom using the cooperative learning model. 2) Activities outside of learning, such as extracurricular activities, can help students develop their soft skills. 3) The cooperative learning model can be used to teach students basic skills like communication, self-confidence, cooperation, creativity, and critical attitudes.